Multivalent glibenclamide to generate islet specific imaging probes. (January 2016) - Babič, Andrej; Lamprianou, Smaragda; Vinet, Laurent; Stransky-Heilkron, Nathalie; Xayaphoummine, Celine; Campo, Marino A.; Glombik, Heiner; Schulte, Anke; Juretschke, Hans-Paul; Montet, Xavier; Meda, Paolo; Lange, Norbert
Abstract: The monitoring of diabetes mellitus, as it develops and becomes clinically evident, remains a major challenge for diagnostic imaging in clinical practice. Here we present a novel approach to beta-cell imaging by targeting the sulphonylurea receptor subtype 1 (SUR1), using multivalent derivatives of the anti-diabetic drug glibenclamide. Since glibenclamide has a high affinity for SUR1 but does not contain a suitable functional group to be linked to an imaging probe, we have synthesized 11 glibenclamide derivatives and evaluated their affinity to SUR1 in MIN6 cells. The most promising compound has been used to obtain multivalent glibenclamide-polyamidoamine (PAMAM) derivatives, containing up to 15 sulphonylurea moieties per dendrimer. The remaining functional groups on the dendrimers can consecutively be used for labeling with reporter groups for different imaging modalities, thus allowing for multifunctional imaging, and for the modification of pharmacokinetic properties. We synthesized fluorochrome-labeled multivalent probes, that demonstrate in cellular assays affinities to SUR1 in the nanomolar range, superior to native glibenclamide. The probes specifically label MIN6 cells, but not HeLa or PANC-1 cells which do not express SUR1. A very low cytotoxicity of the multivalent probes is demonstrated by the persistent release of insulin from MIN6 cells exposed to high glucose concentrations. Furthermore, the probes display positive labeling of beta-cells of primary mouse and human islet-cells ex vivo and of islets of Langerhans in vivo . The data document that multivalent probes based on glibenclamide derivatives provide a suitable platform for further developments of cell-specific probes, and can be adapted for multiple imaging modalities, including those that are now used in the clinics. Graphical abstract: